Visitors’ constraints for recreation activities at Kota Damansara Community Forest - Rozman, Akmal Muhaimin (2019)
The purpose of this exploratory study was to identify visitors conflicts at Kota Damansara Community Forest (KDCF). This is because KDCF provides multiuse trail for different types of recreational users. A structured design questionnaire was answered by 142 respondents. The questionnaire was design into four sections; (1) trip characteristics and behavior (2) self-motivation (3) user conflict and (4) social demographic. The study shows that the main characteristics of the visitors to KDCF are those who are matured (25-33 years old) and willing to spend an amount of money to pursue recreational activity such as mountain biking. This study also found that visitors were willing to travel far from home on weekends to enjoy leisure time at KDCF. High mean value was recorded for hikers (M= 3.94), trail runners (M= 3.66) and mountain bikers (M=.3.51) on meeting with other user on the same trail. This mean that all these groups see no trouble in sharing the trail with other types of recreation user groups. However, about thirteen percent of respondents raised concerns about their safety in sharing the trail while about ten percent perceived their activities were interrupted by other user groups. Although small in number, their concerns must be addressed by the management to ensure satisfaction will be obtained by the many different user groups in the forest.